Outcome of purse-string versus linear skin closure after ileostomy stoma reversal in terms of stoma sites infection and cosmesis - Danish Ali; Muhammad Zubair; Muhammad Adeel kaiser; Awais Amjad Malik; Imran khokhar; Muhammad Farooq Afzal (Journal of the Pakistan Medical Association, 2021)
Abstract Objective: To evaluate the incidence of infection and patient satisfaction in terms of cosmesis between purse-string closure and the usual linear closure of stoma wound. Method: The experimental randomised clinical trial was conducted December 2017 to December 2018 at the Surgical Unit 1, Lahore General Hospital, Lahore, Pakistan, and comprised patients undergoing ileostomy stoma reversal. The patients were randomised into 2 groups using computer-generated random numbers. Group A underwent purse-string closure, while group B received linear closure. Both groups were followed post-operatively at 1 and 3 months for wound infection. Patient satisfaction was ascertained using standard tools. Data was analysed using SPSS version 20. Results: Of the 72 patients, there were 37(51.4%) in group A and 35(48.6%) in group B. Overall, there were 50(69.4%) males and 22(30.5%) females. Infection occurred in 2(5.4%) group A patients and in 8(22.8%) group B patients (p=0.023). Patients in group A were more satisfied at 3 months post-surgery than patients in group B (p=0.001). Conclusion: Purse-string closure was found to be associated with a lower incidence of wound infection and higher patient satisfaction compared to linear closure. Continuous...